2016
DOI: 10.1210/jc.2015-2860
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of β-Cell Dedifferentiation in Human Type 2 Diabetes

Abstract: The data support the view that pancreatic β-cells become dedifferentiated and convert to α- and δ-"like" cells in human type 2 diabetes. The findings should prompt a reassessment of goals in the prevention and treatment of β-cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
478
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(531 citation statements)
references
References 46 publications
47
478
2
4
Order By: Relevance
“…Similarly to loss of Nkx2.2 in adult mouse β cells, inactivation of NKX2.2 in human islets predominantly led to the upregulation of SST ( Figure 7D). Interestingly, the predominance of insulin-and SST-coexpressing cell populations has been described in several recent studies reporting the presence of polyhormonal cells in islets derived from diabetic individuals (33,35).…”
Section: Discussionmentioning
confidence: 84%
“…Similarly to loss of Nkx2.2 in adult mouse β cells, inactivation of NKX2.2 in human islets predominantly led to the upregulation of SST ( Figure 7D). Interestingly, the predominance of insulin-and SST-coexpressing cell populations has been described in several recent studies reporting the presence of polyhormonal cells in islets derived from diabetic individuals (33,35).…”
Section: Discussionmentioning
confidence: 84%
“…While increased β cell apoptosis may be responsible for the majority of decreased β cell mass in advanced T2DM patients (42,43), recently it has been suggested that an additional mechanism may exist. Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45). While the origin of these dedifferentiated/immature β cells is still controversial in humans (32,43), it is plausible that strategies to suppress β cell apoptosis and/or increase β cell differentiation/maturation would be effective at improving β cell function.…”
Section: Discussionmentioning
confidence: 99%
“…They may include, for example, a switch from expression of insulin to expression of glucagon or somatostatin, indicating that β cell plasticity is largely confined to the islet program. The potential of metabolically stressed β cells to dedifferentiate and then redifferentiate into non-β cell fates was proposed as a novel mechanism underlying reversible β cell failure in diabetes (8,(10)(11)(12)(13). Plasticity between α and β cell fates is supported by the remarkably similar epigenetic states of the 2 cell types (14).…”
Section: Introductionmentioning
confidence: 99%